Effectiveness of using innovative technologies in teaching the morphology of bacteria (Journal of Universal Science Research, 2023)
One of the important requirements for the organization of advanced modern education today is to achieve high results in a short time without spending too much mental and physical effort. Based on the delivery of specific theoretical knowledge to students in a short period of time, the formation of certain activity skills and competencies, control of their activities, assessment of the level of theoretical and practical knowledge acquired by them requires the teacher to demonstrate high pedagogical skills, a new approach to the educational process. requires.